6 months versus 12 months of adjuvant trastuzumab for patients with HER2-positive early breast cancer (PHARE): a randomised phase 3 trial - Pivot, Xavier; Romieu, Gilles; Debled, Marc; Pierga, Jean-Yves; Kerbrat, Pierre; Bachelot, Thomas; Lortholary, Alain; Espié, Marc; Fumoleau, Pierre; Serin, Daniel; Jacquin, Jean-Philippe; Jouannaud, Christelle; et al. (The lancet oncology, 2013)
Since 2005, 12 months of adjuvant trastuzumab has been the standard treatment for patients with HER2-positive early-stage breast cancer. However, the optimum duration of treatment has been debated. We did a non-inferiority trial of a shorter exposure of 6 months versus the standard 12 months of trastuzumab for patients with early breast cancer. We did an open-label, randomised, phase 3 trial in 156 centres in France. Patients with HER2-positive early breast cancer who had received at least four cycles of chemotherapy, had breast-axillary surgery, and had received up to 6 months of trastuzumab (administered by intravenous infusions over 30–90 min every 3 weeks; initial loading dose 8 mg/kg; 6 mg/kg thereafter) before randomisation were eligible. Patients were randomly assigned via central randomisation procedure with web-based software to continue trastuzumab for another 6 months (12 months total duration; control group) or to discontinue trastuzumab at 6 months (6 months total duration; experimental group). Randomisation was stratified by concomitant or sequential administration of trastuzumab with chemotherapy, oestrogen-receptor status, and centre using a minimisation algorithm. The primary endpoint was disease-free survival, with a prespecified non-inferiority margin of 1·15. Analyses were done in the intention-to-treat population. This study is registered at ClinicalTrials.gov, number NCT00381901. 1691 patients were randomly assigned to receive 12 months of trastuzumab and 1693 to receive 6 months of trastuzumab; 1690 patients in each group were included in the intention-to-treat analyses. After a median follow-up of 42·5 months (IQR 30·1–51·6), 175 disease-free survival events were noted in the 12-month group and 219 in the 6-month group. 2-year disease-free survival was 93·8% (95% CI 92·6–94·9) in the 12-month group and 91·1% (89·7–92·4) in the 6-month group (hazard ratio 1·28, 95% CI 1·05–1·56; p=0·29). 119 (93%) of the 128 cardiac events (clinical or based on assessment of left ventricular ejection fraction) occurred while patients were receiving trastuzumab. Significantly more patients in the 12-month group experienced a cardiac event than did those in the 6-month group (96 [5·7%] of 1690 patients vs 32 [1·9%] of 1690 patients, p<0·0001). After 3·5 years follow-up, we failed to show that 6 months of treatment with trastuzumab was non-inferior to 12 months of trastuzumab. Despite the higher rates of cardiac events, 12 months of adjuvant trastuzmab should remain the standard of care. French National Cancer Institute.